2006
DOI: 10.3171/ped.2006.104.5.332
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal damage in hydrocephalus and its restoration by shunt insertion in experimental hydrocephalus: a study involving the neurofilament-immunostaining method

Abstract: Cytoskeletal damage of neurons in hydrocephalus and its incomplete restoration by shunt placement were most significant in the periventricular white matter. This finding may account for the impaired cognitive function seen in children who have shunts and an apparently reconstituted cerebral mantle; therefore, neuronal protection in the early hydrocephalic state should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…There was also a significant effect of the number of shunt revisions (F [3,70] = 2.95, p = 0.039) but not of age (F [1,70] = 2.96, p = 0.09) on RD along the parietal pathways. Post hoc pairwise comparisons indicated that the RD (adjusted for age) along the frontal pathways in cases of 2-4 shunt revisions was significantly higher than for cases of no shunt revisions (t [44] = 2.45, p = 0.016).…”
Section: Radial Diffusivitymentioning
confidence: 83%
See 2 more Smart Citations
“…There was also a significant effect of the number of shunt revisions (F [3,70] = 2.95, p = 0.039) but not of age (F [1,70] = 2.96, p = 0.09) on RD along the parietal pathways. Post hoc pairwise comparisons indicated that the RD (adjusted for age) along the frontal pathways in cases of 2-4 shunt revisions was significantly higher than for cases of no shunt revisions (t [44] = 2.45, p = 0.016).…”
Section: Radial Diffusivitymentioning
confidence: 83%
“…Whereas shunt revision had a statistically significant effect on FA along the frontal pathways (F [3,70] For the parietal pathways, number of shunt revisions …”
Section: Fractional Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal cytoskeleton disruption and axonal transport alteration, which are hallmarks of CNS injury, have been demonstrated in the early stages of both TBI and hydrocephalus (Chovanes et al 1988;Aoyama et al 2006;Kupina et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…ICP control is the mainstay of hydrocephalic management and neuronal recovery can occur if ICP is restored to the normal range in the early stages of the disease process (Aoyama et al 2006). The magnitude of neuronal restoration in hydrocephalus is known to be inversely proportional to the duration of pressure elevation, suggesting that the phenomenon of neuronal tolerance to irreversible injury is lost over time (Boillat et al 1997).…”
Section: Introductionmentioning
confidence: 99%